(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Toxic metals in wastewater when discharge in to the environment can accumulate in vital organs when ingested, and get concentrated through the food chain causing poisonous effects to living organisms. Alumina modified onion peel composite was used in this study as an adsorbent for the removal of lead, nickel, chromium, copper and zinc ions from Fish pond wastewater via adsorption process. Batch adsorption experiments were conducted to examine the effect of adsorbent dosage, pH, adsorbate concentration, and contact time on the adsorption of the cations. The optimum adsorbent dosage was 0.3g, pH was 2, contact time was 60 mins and initial concentration was found to be 10 mg/l. The concentration of metal ions present were analyzed using Atomic Absorption Spectrophotometer. The characterization by Fourier Transform Infrared (FTIR) showed absorbance peaks that correspond to hydroxyl, aldehyde, alkyl, amide and carboxylic acid functional groups. These functional groups helped in enhancing the adsorption of the metal ions. Scanning Electron microscope (SEM) analysis was carried out for the morphological characteristics of the adsorbent, before and after adsorption. The experimental isotherm data were analyzed using linear form of Langmuir and Freundlich isotherm models. The Langmuir isotherm provided the best fit for the sorption of Zn2+, Cu2+, Cr3+ and Pb2+ ions with the correlation coefficient (R2) as 0.981, 0.994, 0.9192 and 0.9478 respectively while the Freundlich isotherm had a best fit for the sorption of Ni2+ with the correlation coefficient (R2) of 0.9574. The maximum monolayer adsorption (qm) for copper was found to be the highest